Synthesis of tyrosinase inhibitory (4-oxo-4H-pyran-2-yl)acrylic acid ester derivatives - Kang, Soo Sung; Kim, Hyoung Ja; Jin, Changbae; Lee, Yong Sup (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Melanogenesis is a physiological process that results in the production of melanin pigment. However, excessive accumulations of epidermal pigmentation can cause various hyperpigmentary disorders such as, melasma and age spots. Kojic acid and hydroxylated cinnamic acid derivatives are known to inhibit tyrosinase, a key component of melanin biosynthesis. Pyronyl-acrylic acid esters 3a-i, which share structural features of kojic acid and hydroxylated cinnamic acid, were prepared and their abilities to inhibit tyrosinase and melanin production were evaluated. Of the esters synthesized, 3e and 3h, which derived from diethylene glycol moieties were found to inhibit melanin production by ca. 20% at 20 mu g/ml, whereas kojic acid at 200 mu g/ml inhibited melanin production by 15.8%. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: KOJIC ACID; MELANOCYTE-TYROSINASE; TOXICITY